2000
DOI: 10.1089/108729100416623
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infected Women and Prenatal Care Utilization: Barriers and Facilitators

Abstract: In an effort to understand issues affecting prenatal care access and utilization from the perspectives of human immunodeficiency virus (HIV)-infected women who receive inadequate prenatal care, we conducted three in-depth qualitative and quantitative interviews. From a thematic analysis of the narrative interviews, four broad areas emerged as pertinent to these women's prenatal care experiences. These were issues related to pregnancy, HIV, psychosocial conditions, and the health care system. For these women, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…A literatura internacional cita obstáculos ao acesso à atenção em saúde vivenciados por pessoas vivendo com HIV/AIDS, entre eles: desigualdades sócio-econômicas 11,17,18,19,20,21 disparidades étnicas e de gênero 9,19,20,21,22 , disponibilidade de recursos sociais e financeiros 18,20,21,23 , barreiras geográficas, diferenças culturais entre profissionais de saúde e usuários 19 , receio ou vivência real de estigma 18,19,21,24 .…”
Section: Acquired Immunodeficiency Syndrome; Health Services Accessibunclassified
See 2 more Smart Citations
“…A literatura internacional cita obstáculos ao acesso à atenção em saúde vivenciados por pessoas vivendo com HIV/AIDS, entre eles: desigualdades sócio-econômicas 11,17,18,19,20,21 disparidades étnicas e de gênero 9,19,20,21,22 , disponibilidade de recursos sociais e financeiros 18,20,21,23 , barreiras geográficas, diferenças culturais entre profissionais de saúde e usuários 19 , receio ou vivência real de estigma 18,19,21,24 .…”
Section: Acquired Immunodeficiency Syndrome; Health Services Accessibunclassified
“…Alguns estudos 19,20 associaram acesso à categoria analítica gênero e identificaram idéias e práticas sócio-culturais fundamentadas em diferenças percebidas entre os sexos 28 que, de outra forma, poderiam ser apreendidos apenas parcialmente ou naturalizados no cotidiano das unidades de saúde. A utilização da categoria gê-nero 28 nos estudos sobre acesso e continuidade do uso de serviços de saúde permite pensar criticamente: como concepções e práticas de gênero são social e culturalmente construídas, reconstruídas ou reforçadas nos processos e práticas cotidianas de atenção de serviço de saúde; como imbrincam-se com outros estereótipos e perpetuam ou influenciam desigualdades sociais 28,29 (McCallum, 2005; comunicação pessoal); e como interferem no acesso e continuidade de uso dos serviços.…”
Section: Acquired Immunodeficiency Syndrome; Health Services Accessibunclassified
See 1 more Smart Citation
“…The women carefully choose to disclose their HIV status to those family members or friends who will offer support and suppress disclosure when they fear some form of retribution, including partner violence and withdrawal of emotional or financial support (Njie-Carr et al, 2013). Napravick et al (2000) found lack of support along with unplanned pregnancy, poverty, periodic homelessness, addiction to illicit substances, perceptions of the health care system as threatening, and HIV-related mental health problems (e.g., self-reported depression and isolation) as the most important barriers to access prenatal care.…”
Section: Maternal Health Behaviors Among Pregnant Women With Hiv/aidsmentioning
confidence: 98%
“…Does attending to this prenatal relationship promote her health behaviors by focusing on the woman-identified aspirations and possibilities, rather than the expert-identified barriers and problems (Saleebey, 2006) in general, to poor health practices among HIV-infected women (Demas et al, 2005;Mellins et al, 2003). Napravick et al (2000) using a deficit-based framework found that lack of support and unplanned pregnancy were among the most important barriers for HIV-infected women in accessing prenatal care. However, when extrapolating and comparing findings from previous research one must be critical about several issues related to definitions of the predictor variables, and ecological differences among the cohorts of HIV-infected women investigated in each study.…”
Section: Associations Between Maternal-fetal Attachment and Health Bementioning
confidence: 99%